Water and alcohol-soluble octakis-metalloporphyrazines bearing sulfanyl polyetherol substituents: Synthesis, spectroscopy and electrochemistry - (:unkn) unknown (ELSEVIER SCI LTD, 2007)
Water-soluble metalloporphyrazines (2, 3, and 4) bearing peripherally functionalized bis[thioethoxy(ethoxy)ethanol] moieties have been prepared from the corresponding [2H]-2,3,7,8,12,13,17,18-octakis{2-[2-2-hydroxyethoxy)ethoxy]-ethylthio} porphyrazine and appropriate metal salts [Zn(acac)(2), CoCl2, MnCl2] in non-aqueous polar solvents such its, alcohol and THF. Multifunctional polyetherolsulfanyl peripheral sites, the exocyclic site of porphyrazines, serve as weak interacting ionophore in a number of metal ions, such as Ag-I and Pd-II. The reactivity of the peripheral groups of MPzs was tested by spectrophotometric titration by Ag-I and Pd-II. The titration resulted in the formation of intractable less soluble black and dark-blue polynuclear porphyrazine complexes. The new compounds have been characterized by elemental analysis, FTIR, H-1 NMR, UV-vis and MS (MALDI-TOF). The voltammetric investigation of the complexes showed common ligand and metal-based redox processes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: water-soluble porphyrazine; zinc; cobalt and manganese; polyetherol; aggregates; metal sensor; electrochemistry; cyclic voltammetry; APPENDED PYRIDINE RINGS; METAL-COMPLEXES; PHTHALOCYANINES; PORPHYRAZINES; TETRA-2,3-PYRAZINOPORPHYRAZINES; MONOAZACROWN; REACTIVITY; BINDING; LIGAND; PD2+